Jab and Straight Punch of Extracurricular Boxing Athlete Panjaguru UPT SMA Negeri 7 Jeneponto - Latuheru, Ricardo Valentino; Ikadarny, Ikadarny (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research is a quantitative descriptive research. The subjects in the study were students of the extracurricular boxing Panjaguru Upt SMAN 7 Makassar. The research instrument used was the Jab And Straight Punch Speed Test. The number of samples used was 15 people. The processing of research data used descriptive statistics while the data analysis technique used was percentage. The results of the study of the ability to pass under the Jab And Straight Punches of Extracurricular Boxing Athletes Panjaguru Upt Sma Negeri 7 Jeneponto, for the